2015
DOI: 10.1016/j.jcmg.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

How to Detect and Treat Coronary Fibroatheromas

Abstract: As you set out for Ithaka hope the voyage is a long one, full of adventure, full of discovery.-Constantine P. Cavafy, Ithaka (1) C oronary fibroatheromas can cause a wide spectrum of adverse events, such as sudden death, acute coronary syndromes, and procedural complications during percutaneous coronary interventions (PCI) (2). Accurate fibroatheroma detection could significantly enhance our ability to treat these lesions and prevent complications. FIBROATHEROMA DETECTION DURING CARDIAC CATHETERIZATION Fibroat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…However, as previously mentioned, the combined NIRS-IVUS-imaging catheter allows co-registration of both IVUS and NIRS data, which gives information on both plaque composition and morphology. NIRS-IVUS has shown to improve LCP detection, by comparison to IVUS, in calcified plaques as well as in lesions with small plaque burden [78]. The combined measures of plaque burden and LCBI improved the accuracy of fibroatheroma detection as compared with plaque burden alone by grayscale IVUS.…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 97%
“…However, as previously mentioned, the combined NIRS-IVUS-imaging catheter allows co-registration of both IVUS and NIRS data, which gives information on both plaque composition and morphology. NIRS-IVUS has shown to improve LCP detection, by comparison to IVUS, in calcified plaques as well as in lesions with small plaque burden [78]. The combined measures of plaque burden and LCBI improved the accuracy of fibroatheroma detection as compared with plaque burden alone by grayscale IVUS.…”
Section: Near-infrared Spectroscopy (Nirs)mentioning
confidence: 97%
“…One autopsy study showed that 52% of IVUS‐detected calcified plaques were actually fibroatheromas on histological analysis . NIRS/IVUS act synergistically to improve tissue characterization in calcified plaques as well as plaques with smaller plaque burden .…”
Section: Identification Of Lipid Core Plaque and Comparison With Othementioning
confidence: 99%